2013
DOI: 10.1177/0267659113497073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of venovenous extracorporeal membrane oxygenation on cerebral oxygenation in hypercapnic ARDS

Abstract: Extracorporeal membrane oxygenation (ECMO) is increasingly used in ARDS patients with hypoxemia and/or severe hypercapnia refractory to conventional treatment strategies. However, it is associated with severe intracranial complications, e.g. ischemic or hemorrhagic stroke. The arterial carbon dioxide partial pressure (PaCO2) is one of the main determinants influencing cerebral blood flow and oxygenation. Since CO2 removal is highly effective during ECMO, reduction of CO2 may lead to alterations in cerebral per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…Recently, Muellenbach et al reported that patients receiving vvECMO treatment were at risk for a decrease in cerebral regional tissue oxygen saturation at ECMO initiation, and that this decreased is linked to PaCO2 change. This could be involved in the pathogenesis of brain injury of ECMO patients [19,20]. In our study, the acute PaCO 2 change was independently associated with cerebral bleeding and one can hypothesize that these abrupt changes may have facilitated brain hemorrhages.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, Muellenbach et al reported that patients receiving vvECMO treatment were at risk for a decrease in cerebral regional tissue oxygen saturation at ECMO initiation, and that this decreased is linked to PaCO2 change. This could be involved in the pathogenesis of brain injury of ECMO patients [19,20]. In our study, the acute PaCO 2 change was independently associated with cerebral bleeding and one can hypothesize that these abrupt changes may have facilitated brain hemorrhages.…”
Section: Discussionsupporting
confidence: 49%
“…14,[18][19][20][21][22] Particular care should also be devoted to avoid hyperoxia and hypocapnia just after ECLS initiation as the two conditions together may increase brain damage (reperfusion injury) or loss of cerebral perfusion autoregulation. 23,24 After the patient is stabilized, further diagnostic procedures must immediately proceed. A detailed case history must be collected.…”
Section: Post-resuscitation Carementioning
confidence: 99%
“…Nonetheless, it is increasingly evident that the mechanisms underlying the occurrence are not simply linked to embolization, bleeding, or low-flow related brain hypoxia (3)(4)(5) which were thought to represent the sole source of injury of the brain in ECLS patients.…”
mentioning
confidence: 99%
“…Furthermore, the mechanisms underlying the high rate of cerebral hemorrhage experienced in V-V subjects might be different from the same event observed in V-A patients, who, instead, have higher rates of brain death and ischemic injury. The importance of altered blood gases, particularly of CO 2 clearance, in the genesis of neurologic adverse events has been underlined by several investigators (4,5,13).…”
mentioning
confidence: 99%